Demand Forecasting Model dengan Pendekatan Sistem Dinamis untuk Mendukung Analisa Finansial dalam Pengembangan Infrastruktur Bandar Udara di Indonesia - Eny Yuliawati (Research and Development Agency of The Ministry of Transportation, 2015)
Pertumbuhan penumpang angkutan udara mengalami peningkatan sejalan dengan pertumbuhan penduduk dan perekonomian di suatu negara. Revenue passenger kilometers (RPK) wilayah Asia Tenggara dalam kurun waktu 10 Tahun (2000-2010) adalah sebesar 6,6 % per tahun. Pertumbuhan penumpang angkutan udara yang sangat pesat tersebut harus diimbangi dengan penyediaan infrastruktur transportasi udara, Namun saat ini alokasi anggaran pemerintah di bidang infrastruktur transportasi sangat terbatas.untuk itu diperlukan berbagai instrumen kebijakan apabila ingin melibatkan peran swasta. Salah satu upaya untuk mendukung keterlibatan peran swasta dapat dikembangkan model “demand forecasting” menggunakan pendekatan sistem dinamis guna mendukung analisa finansial dalam pengembangan infrastruktur bandar udara. Dengan model demand forecasting penumpang angkutan udara yang komprehensif tersebut diharapkan dapat membantu dalam menganalisa pengambilan sebuah keputusan dalam pengembangan bandar udara yang melibatkan peran serta investasi swasta. [Demand Forecasting Model with Dynamic Systems Approach to Support Financial Analysis in the Airport Infrastructure Development in Indonesia] The growth of air passengers has increased in line with the population and economic growth of the country. Revenue passenger kilometers (RPK) around in the world during ten years (2000-2010) grew on average of 4.7 % per year, and in the Southeast Asian region. RPK growth in the same period was 6.6% per year. The growth of passenger air transport is very rapid course must be balanced with the provision of air transport infrastructure, while the government budget in transport infrastructure sector has a constraint. Development of airports in Indonesia is still a burden for the reason it, needed the government's policy instruments if want to involve the role of private sector in the airport development. The one of policy istruments is define a model demand forecasting using a dynamic systems approach to support financial analysis in the development of airport infrastructure. Air traffic analysis is an important thing because concerning with the capacity utilization and it helps make decisions regarding the development of infratructure facilities. The robust model of demand forecasting could support to analyze a decision making on an airport development that involves the participation of private investment.